KECERDASAN SPIRITUAL DITINJAU DARI NILAI NILAI PROFETIK - Umam, Muhamad Khoirul; Saputro, Eko Andy (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2020)
Spiritual Quotient (SQ) is a person's ability to understand and give meaning to what is encountered in life, so that someone will have flexibility in dealing with problems in society. Spiritual Quotient (SQ) plays a role in humans in relation to life and religion. Therefore in this article the author will explain a little about the SQ whose main model is the best creature ever created by Allah, the Prophet Muhammad. With the formulation of the problem Understanding of Spiritual Intelligence, Characteristics of Spiritual Intelligence, Benefits of Spiritual Intelligence, Prophet Muhammad SAW As an Example of the Spiritual Intelligence of Muslims.Keywords: Spiritual Quotient, Characteristics, life and religion